A new species of eriophyoid mite (Acari: Eriophyoidea) on Rosa sp. from Israel - Druciarek, Tobiasz; Lewandowski, Mariusz (Zootaxa, 2016)
A new species of eriophyoid mite from a hybrid of Rosa sp. (Rosaceae) found in Israel is described and illustrated. Eriophyes eremus n. sp. is a refuge-seeking type mite, inhabiting flower buds and petiole bases, causing no apparent damage to the host plant. Eighteen eriophyoid species are known to inhabit Rosa sp. and those are listed here along with type localities, damage they cause and host plant details.